2012
DOI: 10.1002/jso.23245
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic significance of serum MicroRNAs in colorectal cancer

Abstract: MicroRNAs are short non-coding RNA molecules involved in the regulation of gene expression. There are few studies related to the determination of serum microRNAs in colorectal cancer. The identification of microRNAs in peripheral blood as noninvasive markers of tumor disease may lead to potential applications, although further clinical studies focusing on serum microRNAs are required to determine their clinical significance for the diagnosis and prognosis outcome of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 33 publications
1
14
0
3
Order By: Relevance
“…These findings suggest that miRNAs may play a role in promoting or inhibiting tumour development. [19][20][21][22] Tang et al 23 investigated miRNA expression in adipose stromal cells and found that miR-22 played an important role in regulating the development of these cells. miR-22 was aberrantly expressed in many tumour tissues, including breast cancer, colorectal cancer and cervical carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that miRNAs may play a role in promoting or inhibiting tumour development. [19][20][21][22] Tang et al 23 investigated miRNA expression in adipose stromal cells and found that miR-22 played an important role in regulating the development of these cells. miR-22 was aberrantly expressed in many tumour tissues, including breast cancer, colorectal cancer and cervical carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Specific miRNAs function as negative or positive regulators of genes involved the development of tumor types (He et al, 2004;Bartel., 2009), such as lung cancer (Du et al, 2012), colorectal cancer (Menéndez et al, 2013), breast cancer (Liu., 2009), and gastric cancer (Wu et al, 2014). Gastric cancer is a major malignant tumor type, representing the second most common cancer and the leading cause of cancer mortality worldwide.…”
Section: Macrophage-secreted Exosomes Delivering Mirna-21 Inhibitor Cmentioning
confidence: 99%
“…In a groundbreaking work, Mitchell et al [38] have demonstrated that circulating miRNAs are present in the human blood, where they are carried in complex with the chaperon argonaute 2 and/or lipoproteins or by microvesicles, conferring stability and protection against RNases [39]. Correlations exist between blood miRNA levels and pathologies, indicating that miRNAs are potential noninvasive biomarkers [40]. It is thus reasonable to hypothesize that miRNA seric or plasma expression is a most promising avenue to evaluate early risk and patient outcome, but also individual patient response to various treatments or surgical procedures.…”
Section: Rna-based Mechanismsmentioning
confidence: 99%